Peran Moderasi Human Capital Diantara Pengaruh PMA dan PMDN Terhadap Pertumbuhan Ekonomi - Islahul amri; Misbahul Munir (Ekspansi: Jurnal Ekonomi, Keuangan, Perbankan, dan Akuntansi, 2020)
Investment and development of human capital is a major concern for the current government. By increasing the value of domestic and foreign investment and the competence of human capital will increase Indonesia's economic growth. The purpose of this study is to determine the effect of domestic investment and foreign capital investment on economic growth with moderated human capital. This research uses a quantitative approach. The number of samples selected amounted to 10 samples obtained from time series data during the period 2010- 2019. Data analysis methods used were multiple regression analysis and the Moderated Regression Analysis (MRA) test. From the results of the study indicate that domestic investment has a positive and significant effect on the money supply. Foreign Investment has a positive and not significant significant effect on the money supply. Human capital is not able to moderate the relationship of Domestic Investment to economic growth. While human capital can moderate the relationship of Foreign Investment to economic growth.